2019
DOI: 10.1007/s00787-018-01273-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental health difficulties, attainment and attendance: a cross-sectional study

Abstract: Evidence for the association between mental health difficulties and academic outcomes is sparse and shows mixed results. The aim of this study was to investigate the association between educational attainment, absenteeism and mental health difficulties while controlling for various child characteristics such as special education needs and socioeconomic background. 15,301 year 7 pupils (mean age: 11.91; SD = 0.28) from England completed the Strengths and Difficulties Questionnaire. Attainment, persistent absent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 13 publications
2
19
0
2
Order By: Relevance
“…In the overall student population, the association between poverty and exclusion is well established (e.g. Lereya & Deighton, 2019), but our data provide a more nuanced picture of socioeconomic correlates of school exclusion. We found a higher risk of school exclusion among single-parent, unemployed and well-educated parents.…”
Section: Discussionmentioning
confidence: 69%
“…In the overall student population, the association between poverty and exclusion is well established (e.g. Lereya & Deighton, 2019), but our data provide a more nuanced picture of socioeconomic correlates of school exclusion. We found a higher risk of school exclusion among single-parent, unemployed and well-educated parents.…”
Section: Discussionmentioning
confidence: 69%
“…Our findings suggest that greater consideration should be given to the provision of counselling in primary schools. Early intervention at this young age, before mental health problems become entrenched in adolescence and young adulthood, may help to prevent the long-term impacts of childhood mental health problems, including adverse educational outcomes [12][13][14]. Children who received the counselling intervention were similar in terms of their mental health to individuals from a national population survey who had been in contact with specialist mental health and/or education services (see Table S6 in online supplementary information).…”
Section: Discussionmentioning
confidence: 99%
“…Children who are well educated have better health and wellbeing, while those with better health, including better mental health, perform better at school [11]. Children with mental health problems have poorer academic attainment, greater school absences, and an increased risk of school exclusion compared to their mentally healthy peers [12][13][14]. Recent research by the Institute for Public Policy Research showed that parents would like greater priority to be given to school-based mental health support, while more than 70% of teachers believed greater access to onsite mental health support would improve student attainment [15].…”
mentioning
confidence: 99%
“…In the second stage of the psychiatrists' training program, only three months may be spent in child and adolescent psychiatry [14]. Thirdly, the mental healthcare system for children needs further development requiring collaboration at all levels of society, including schools, communities, hospitals, the regional Center for Disease Control and Prevention, and the local government [5,6]. However, difficulties still exist in implementing various policies and related activities due to the lack of cooperation and coordination among different institutions and organizations.…”
Section: Main Challenges For Improvement Of the Mental Healthcare Sysmentioning
confidence: 99%